Productivity and seed quality of hybrid rice (Oryza sativa L.) genotypes as influenced by age of seedling and spacing under SRI - Singh, Rajiv K.; Upadhyay, P.K.; Rathore, S.S.; Singh, S.K.; ., Saurbh (Annals of Agricultural Research, 2018)
A field experiment was conducted during rainy season (2014) to evaluate the effect of age of seedlingsand spacing on growth, yield and yield attributes and seed quality of hybrid rice (Oryza sativa L.)under system of rice intensification. The 8 treatments were laid out in split plot design, keepingcombinations of two hybrid (DRRH-2 and DRRH-3) and seedlings age (12 and 25 days old) in mainplots and two spacings (25×25 cm and 20×15 cm) in sub-plots with 3 replications. The hybrid ricegenotype DRRH-3 was significantly superior than DRRH-2 with respect to growth parameters,yield attributes, seed yield and seed quality. Among the age of seedlings, 12 days old seedlingsregistered higher growth, yield & yield attributes and seed quality parameters and it produced 1.23q/ha more seed yield than 25 days old seedlings. Similarly wider row spacing of 25×25 cm recordedhigher growth parameters, yield attributes, seed yield, seed quality and soil health due to profuseroot growth. Among the hybrid rice, root length (cm), shoot length (cm) & seedling dry weight (g)were higher in DRRH-3 (20.22, 11.98 & 0.772, respectively) and vigour index-II (66.9) was highest inDRRH-2.